Exercise Training in Elderly People Undergoing Hemodialysis: A Systematic Review and Meta-analysis - Ryota Matsuzawa; Keika Hoshi; Kei Yoneki; Manae Harada; Takaaki Watanabe; Takahiro Shimoda; Shuhei Yamamoto; Atsuhiko Matsunaga (Kidney International Reports, 2017)
Previous reviews have indicated the effectiveness of exercise in people undergoing hemodialysis. However, these analyses did not take into account whether the subjects were elderly. We performed a systematic review of the effects of exercise training in elderly people undergoing hemodialysis and updated the evidence of exercise for people undergoing hemodialysis by adding recent research data. Methods: We searched 8 electronic databases up to June 2016. Inclusion criteria were as follows: randomized controlled trial, English publication, subjects aged 18 and older undergoing hemodialysis, evaluation of physical function as an outcome of exercise intervention. We defined elderly as age 60 years and older. The main outcomes were exercise tolerance (peak/maximum oxygen consumption) and walking ability (6-minute walk distance). Secondary outcomes were lower extremity muscle strength and quality of life. Results: After screening of 10,923 references, 30 comparisons were entered into the analysis. However, because we found only 1 study in which elderly subjects were treated, we could not perform a meta-analysis for these people. For the general population undergoing hemodialysis, supervised exercise training was shown to significantly increase peak/maximum oxygen consumption (standard mean difference, 0.62; 95% confidence interval 0.38–0.87; P < 0.001), 6-minute walk distance (standard mean difference, 0.58; 95% confidence interval 0.24–0.93; P < 0.001), lower extremity muscle strength (standard mean difference, 0.94; 95% confidence interval 0.67–1.21; P < 0.001), and quality of life (standard mean difference, 0.53; 95% confidence interval 0.52–0.82; P < 0.001). Discussion: Our analysis on the effectiveness of exercise training in elderly people undergoing hemodialysis as compared with nonelderly people was somewhat inconclusive. Future studies should be carried out for elderly people to identify the most favorable exercise program for this population.